Rhizobial lipochitooligosaccharide nodulation factors activate expression of the legume early nodulin gene ENOD12 in rice - Reddy, Pallavolu M.; Ladha, Jagdish K.; Ramos, Marilou C.; Maillet, Fabienne; Hernandez, Rowena J.; Torrizo, Lina B.; Oliva, Norman P.; Datta, Swapan K.; Datta, Karabi (Wiley, 1998)
Lipochitooligosaccharide nodulation factors (Nod factors) produced by rhizobia are a major host range determinant. These factors play a pivotal role in the molecular signal exchange, infection and induction of symbiotic developmental responses in legumes leading to the formation of a nodule in which rhizobia carry out N2 fixation. Determining whether rice ( Oryza sativa) can respond to Nod factors could lead to strategies that would make rice amenable to develop a nitrogen‐fixing endosymbiotic association with rhizobia. We introduced into rice the promoter of the infection‐related gene MtENOD12 (from Medicago truncatula) fused to the β‐glucuronidase (GUS) reporter gene to serve as a molecular marker to aid in the detection of Nod factor signal perception by rice cells. Treatment of the transgenic rice roots with Nod factors (10–6–10–9m) under nitrogen‐limiting conditions induced MtENOD12‐GUS expression in cortical parenchyma, endodermis and pericycle. In contrast, chitooligosaccharide backbone alone failed to elicit such a response in the root tissues. These findings demonstrate that rice roots perceive Nod factors and that these lipochitooligosaccharides, but not simple chitin oligomers, act as signal molecules in activatingMtENOD12 in cortical parenchyma as in legumes. Exogenous application ofN‐naphthaleneacetic acid mimicked the Nod factor‐elicited tissue‐specific expression ofMtENOD12 in roots while cytokinins inhibited it, thus evidencing that Nod factors, auxin and cytokinins probably act on similar signaling elements responsible for the regulation ofMtENOD12 activation in rice. Taken together, these results suggest that at least a portion of the signal transduction machinery important for legume nodulation is likely to exist in rice.